PELAYANAN KEPENDETAAN DAN KEAKTIFAN JEMAAT DALAM PERIBADATAN - Alan Hubert Frederick Sanger; Frans Sanger; Juwinner Dedy Kasingku; Yornal Buladja (Nusantara Hasana Berdikari, 2022)
This study attempts to determine the level of the pastor's ministry, the level of the congregation's participation in worship, and whether there is a significant relationship between the pastor's ministry and the congregation's involvement in worship. The instrument used is a questionnaire for the pastor's ministry that was modified from Wentuk (2013), and a